Virulence genes detection among the antibiotic resistant Enterococcus faecalis isolated from bird industry in Borneo - Leong, Sui Sien; Lihan, Samuel; Chia, Hwa Chuan (Universiti Putra Malaysia Press, 2020)
The abuse of antibiotics usage in bird industry has resulted in the emerging antibiotic resistant Enterococci worldwide which has posed a threat clinically to human health. The present study was to screen and identify the potential virulence agents in antibiotic resistance E. faecalis in bird industry in Borneo. Enterococcus bacteria collected from the birds’ faeces and indoor air inside ten birdhouses were identified to species level and their antibiotic resistance was checked using antibiotic susceptibility discs. Specific primers using PCR assay were intended for the detection of four potential virulence genes (ace, AS, efaA, gelE). Out of the thirty-seven Enterococci faecal bacteria, the prevailing bacteria found were Enterococcus qallinacum (51%), Enterococcus faecalis (35%) and Enterococcus harae (8%). The airborne bacteria were reported as Enterococcus faecalis (5%) and Enterococcus qallinacum (1%). Twenty-seven percent of isolates were reported to have Multiple Antibiotic Resistance (MAR) index ≥ 0.2 with 9 distinct resistance patterns formed. E. faecalis showed higher resistance to vancomycin. Virulence genes were successfully reported in the 15 E. faecalis isolates. Sixty-seven percent of isolates were detected positive for four virulence genes, 27% possessed three (AS, efaA, gelE) genes and 6% possessed two (ace, AS) genes. Antibiotic resistance and virulence genes detection were significantly correlated. These virulence genes or antibiotic resistance genes were important in the pathogenesis of E. faecalis infections.